Strategic collaboration between UMP and Seeloz in developing AI technology - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 25 March 2022 - Artificial intelligence (AI) technology is a crucial cutting-edge technology that helps improve supply chain and production efficiency in line with the idea of implementing the fourth Industrial Revolution (IR4.0).